Sleep patterns in rats - Hoshino, Katsumasa [UNESP]; Andersen, Monica Levy; Papale, Ligia Assumpção; Alvarenga, Tathiana Aparecida Fernandes (Springer Nature, 2015)
The rat, a mammal of the Rodentia order that encompasses several species with the most ubiquitous being the brown rat (Rattus norvegicus) and the black rat (Rattus rattus), is present in all latitudes of the globe. Thanks to their tremendous ability to withstand and survive adverse conditions, the rat has been used in biological experimentation for a 100 years. In the first half of the twentieth century, several breeds and strains were created through successive breeding between males and females that possessed specific characteristics. These have been utilized in distinct fields of research because of their known genetic properties. Today, the most widely used experimental animal is the albino rat, selected at the Wistar Institute of Philadelphia, whose fur is entirely white (hence the name albino rat or the Wistar rat). This strain, called Rattus norvegicus albinus, is characterized by the complete absence of melanin in the fur and in the iris. The word albino derives from the Latin adjective albus, meaning white.